2019
DOI: 10.1080/15305058.2019.1635604
|View full text |Cite
|
Sign up to set email alerts
|

Stopping Rules for Computer Adaptive Testing When Item Banks Have Nonuniform Information

Abstract: The standard error (SE) stopping rule, which terminates a computer adaptive test (CAT) when the SE is less than a threshold, is effective when there are informative questions for all trait levels. However, in domains such as patient reported outcomes, the items in a bank might all target one end of the trait continuum (e.g., negative symptoms), and the bank may lack depth for many individuals. In such cases, the predicted standard error reduction (PSER) stopping rule will stop the CAT even if the SE threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
2
0
2
Order By: Relevance
“…Patients with no problems or disease symptoms have to answer a maximum of 12 questions to reach the CAT stopping rule. Adjustments to this stopping rule should be evaluated to explore if it is possible to reduce questionnaire burden [ 61 ]. Second, other aspects of feasibility such as the comprehensibility of the PROMIS CATs and SF-36v2 in patients with low health literacy and the cost for administration should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with no problems or disease symptoms have to answer a maximum of 12 questions to reach the CAT stopping rule. Adjustments to this stopping rule should be evaluated to explore if it is possible to reduce questionnaire burden [ 61 ]. Second, other aspects of feasibility such as the comprehensibility of the PROMIS CATs and SF-36v2 in patients with low health literacy and the cost for administration should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…For each individual, a difference was considered meaningful if the absolute value of this difference exceeded 0.3 (Fyffe et al, 2011; Gibbons et al, 2017). This commonly used precision threshold comes from the standard error stopping rule in the computer adaptive testing literature (Morris et al, 2020), which corresponds to a reliability of .9 (Nunnally & Bernstein, 1995). If greater than 5% of the overall sample exhibited meaningful differences, then it was concluded that the identified measurement noninvariance was salient and should not be ignored in any group comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…This enforces a hard constraint on its stopping time. Even though some investigations introduce an adaptive stopping time [45][46][47][48], the stopping time may not exceed the number of items in the pool. In contrast, we consider an infinite-horizon setting, in which each experiment can be sampled as many times as necessary.…”
Section: Related Literaturementioning
confidence: 99%